The Influence of Government Support and Innovative Work Behaviour on Customer Relationship Management and its Implications on Marketing Result: A Study at PT BPRS Bhakti Sumekar Sumenep - Inggit Mawarsih Puspita Sari; Whony Rofianto; Enny Haryanti; Antyo Pracoyo (Jurnal Global Ilmiah, 2026)
Despite the critical role of regional government owned Islamic Rural Banks (Bank Perekonomian Rakyat Syariah/BPRS) in advancing local financial inclusion, empirical understanding of how government support shapes innovative organizational behavior and, through it, customer relationship management quality and marketing performance remains limited. This study examined the influence of Government Support on Individual and Organizational Innovative Work Behaviour (IWB), the subsequent effects of both IWB dimensions on four Customer Relationship Management (CRM) components: Customer Orientation, CRM Organization, CRM Knowledge Management, and Technology-Based CRM, and the implications of these CRM dimensions for Marketing Result. A quantitative explanatory design was adopted, with data collected from 129 purposively sampled employees and analyzed by Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that Government Support positively and significantly influences both Individual and Organizational IWB, with the latter demonstrating stronger downstream effects on all CRM dimensions. Among the CRM components, Customer Orientation and Technology-Based CRM emerged as the most consequential pathways to improved Marketing Result, with the model explaining a substantial proportion of variance in the outcome variable. These results establish Government Support as a strategic institutional resource that catalyzes innovative work behaviour, and identify Technology-Based CRM as the most effective mechanism for enhancing marketing performance in government-owned BPRS. The study extends the model of Nicolescu and Ripa (2024) by incorporating Government Support as an upstream antecedent, offering theoretical contributions to the CRM and innovation literature and practical implications for regional governments and banking regulators.